PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PT. JABABEKA, Tbk - Adriana Syariefur Rakhmat (Jurnal Pengembangan Wiraswasta, 2018)
Firm’s value is investor perception of the company, which is often associated with stock prices, higher stock prices could increase the firm’s value. Firm’s value is proxied by Price Book Value (PBV) which is a market ratio used to measure the performance of the stock prices to it’s book value. The present study is aimed at finding out the influence of profitability proxied by Return On Equity  (ROE) and capital structur  proxied by Debt to Equity Ratio (DER) on firm’s value.The population of the study are quarterly financial statements on PT. Jababeka, Tbk that were listed at Indonesian Stock Exchange in year period of 2011 – 2015. Testing the hypothesis in this study using a software toll SPSS (Statistical Product and Service Solution) version  22.The result of this study showed that : (1)  profitability positively and significantly influence firm’s value; (2) capital structure positively and significantly influence firm’s value; (3) profitability and capital structure significantly influence firm’s value. Keywords:Price Book Value, Return On Equity, and Debt to Equity Ratio